Professional secrecy and confidentiality in sexual and reproductive health services provision - Briozzo, Leonel (2015)
Background: Medical secrecy originates in the Hippocratic Oath. Medical ethics codes around the world demand the observance of confidentiality and professional secrecy and laws from different countries support them as part of persons’ rights. Therefore it is imperative to reconstruct values in our profession and to become again allied with our patients by respecting their rights. Professional secrecy is a value. It assures fidelity of professionals with patients, generates confidence conditions, assures intimacy so that all men and women may be truthful without fear and assures respect to persons’ liberty in regards to their personal choices and individual rights. Medical secrecy has to be analyzed in the frame of physician-patient relationship. In particular in what refers to health and sexual and reproductive rights, like unwished and untimely pregnancy, induced abortion in risk conditions, lack of adequate sexual and reproductive health services, domestic and sexual violence, sexual transmission infections and HIV. Lack of respect of information confidentiality may affect both men and women, but more frequently it may dissuade women to obtain advice and treatment and consequently affect negatively her health and wellbeing. Hence medical duty to rescue this value.